Spontaneous Heterotopic Triplet Pregnancy with a Two Viable Intrauterine Embryos and an Ectopic One with Right Tubal Rupture - Adriano Carvalho Guimarães; Luciano Dias de Oliveira Reis; Fabio Chaves Leite; Cassiana Franco Dias dos Reis; Alex Paula Costa; Walter Junior Boim de Araujo (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Heterotopic pregnancy (HP) is defined as the simultaneous development of an intra- and an extra uterine gestation. The occurrence of a spontaneous triplet HP is an exceptionally rare medical condition. We report the case of a young woman with spontaneous heterotopic triplets at 8weeks of gestation, with amisdiagnosis of topic twins and acute appendicitis. The ectopic tubal pregnancy was ruptured and a salpingectomy was performed by laparotomy. The intrauterine pregnancy progressed uneventfully. The two healthy babies were delivery by cesarean section at 36 ± 2 weeks of gestation. Heterotopic triplets with ruptured tubal ectopic pregnancy represent a special diagnostic and therapeutic challenge for the obstetrician. A high rate of clinical suspicion and timely treatment by laparotomy or laparoscopy can preserve the intrauterine gestation with a successful outcome of the pregnancy.